Effects of ultraviolet irradiation on physicochemical, microbiological, and rheological properties of pineapple (Ananas comoscus L. var. yankee) juice - Chia, Su Ling (2011)
Unpasteurised or fresh juice may be contaminated with pathogens or microorganisms that are harmful to human health. Presently, thermal pasteurisation is the most common technology used in the fruit juice industry to inactivate enzymes or microorganisms, but the application of heat adversely affect the nutritional and sensory qualities of the juice. Ultraviolet (UV) irradiation is a promising disinfection technology. This nonthermal technology minimizes the loss of flavour and nutritional qualities of fruit juice. There is no literature available about the application of UV to pineapple juice. The present study aims to investigate the effect of UV irradiation on the quality of pineapple juice based on physicochemical, microbiological and rheological analyses. A UV dosage of 53.42 mJ/ cm2 administered to the pineapple juice was chosen based on germicidal effectiveness. The UV-irradiated pineapple juice was similar to the untreated juice in total soluble solids (TSS), pH, titratable acidity, ascorbic acid, L*, hue angle and chroma parameters, but was significantly different (p<0.05) compared to the thermally pasteurised pineapple juice. Turbidity of pineapple juice was significantly decreased (p<0.05) after UV treatment and significant increased (p<0.05) after the thermal treatment. A large and significant reduction (p<0.05) in the total phenolic content was seen in the thermal treatment group (34.83%) as compared to the UV-irradiated group (16.55%). There was a significant decrease (p<0.05) in the total plate counts (TPC) and the yeast and mould counts (YM) in the UV and the thermally treated pineapple juice, although the thermally treated group was statistically more variable than the UV treatment group. During the 13 weeks of storage, TSS and titratable acidity of UV-irradiated juice were significantly decreased (p<0.05) whereas pH and turbidity were significantly increased (p<0.05). However, these parameters remained stable in thermally pasteurised juice throughout the storage time. There were no significant changes in total phenolic for both treatments throughout the storage period. Other quality parameters (ascorbic acid, L*, hue angle and chroma) were significantly affected by the storage time in the UV-irradiated and thermally pasteurised juice. Regarding the microbiological analysis, the TPC and YM of the UV-irradiated juice increased gradually throughout the 13 weeks of storage while these parameters remained unchanged in the thermally pasteurised juice with almost no microorganism growth. A rheological test was performed on untreated, UV-irradiated and thermally pasteurised juice at temperatures ranging from 5°C to 25°C throughout the 13 weeks of storage. The Bingham model described adequately the rheological behaviour of he juices. There was no significant variation between the plastic viscosities of the untreated and UV-irradiated juice at all temperatures. A significant (p<0.05) increase of plastic viscosity was however observed in the thermal pasteurised juice at temperature 5°C and 10°C. Throughout the 13 weeks of storage, plastic viscosities of untreated and UV-irradiated juice in the temperature range of 5°C to 25°C significantly decreased while no significant change was found in thermally pasteurised juice. The effect of temperature on plastic viscosity was adequately described by the Arrhenius equation. The results of this study demonstrate the effectiveness of UV irradiation in preserving the nutritional quality attributes of fruit juice compared to thermal pasteurisation.